KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS XII IPS SMA NEGERI 1 PAYAKUMBUH DALAM PEMBELAJARAN MATEMATIKA DENGAN MODEL THINK-PAIR-SHARE BERBANTUAN VIDEO ANIMASI - Lestari, Nicke Indah (Departemen Matematika, 2023)
Mathematics demands mathematical communication skills to express ideas appropriately. Mathematical communication skills remain poor. According to observations. The Think Pair Share cooperative learning methodology with animated video was chosen. Mathematical communication abilities were examined better utilizing the Think Pair Share video animation model than a direct model in class XII IPS SMA Negeri 1 Payakumbuh. Study employed Nonequivalent Posttest-Only Control Group Design. Sampling was random. Experimental and control classes were XII IPS 1 and 2. The research hypothesis was supported by Mann-Whitney. The P-value from data analysis is 0,022. H0 was rejected due to a P-value . Think Pair Share cooperative learning using animated video to improves mathematical communication more than direct learning.Keywords – Think Pair Share, Mathematical Communication Skills, Animated Videos, Direct Learning